Test dlya otsenki ballisticheskoi koordinatsii dvigatel'noi deyatel'nosti - Bulkin, V. A.; Popova, E. V.; Saburova, E. V. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study was to foundate and elaborate the complex unified test for jump (ballistic) coordination. As a result the dynamic bundle of jumps had been offered to be performed with time and space accuracy registration. The nomograms of evaluation values of jump's length and time are calculated. The evaluation zones are determined by coefficient of coordination's integtrative index.